Pengaruh Return On Equity Ratio, Current Ratio, Dan Dividend Yield Terhadap Harga Saham Perusahaan Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Fina Nur Aulia Saragih; Ermalina Ermalina (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
This study aims to examine the analysis of the effect of Return On Equity Ratio (ROE), Current ratio, and Dividend yield on Company Stock Prices in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange (IDX). The sample selection in this study using purposive sampling method and obtained 12 companies that match the criteria. The research data was obtained from the Indonesia Stock Exchange. The results of this study are the adjusted R-Square value of 44.1%. Partially it shows that the Return on Equity Ratio (ROE) and Dividend yield variables have a positive influence on stock prices, while the Current ratio variable also has an influence on stock prices, but not partially. Then, the variables Return on Equity Ratio (ROE), Current ratio, and Dividend yield have a joint or simultaneous effect on stock prices.